Council of Scientific and Industrial Research: Opportunity to the field of Pharmacy - A. Krishnaveni; G.R.Kaviyavikashini; M. Vijay; P.Gowri Manohari; T.Venkatarathina Kumar; A. Abdul Hasan Sathali (International Journal of Pharmacy and Analytical Research, 2022)
CSIR covers a wide spectrum of science and technology departments such as oceanography, geophysics, chemicals, drugs, genomics, biotechnology and nanotechnology to mining, aeronautics, instrumentation, environmental engineering and information technology. CSIR is the only Indian organization among the top 100 global government institutions ranked 37th among 1587 government institutions Worldwide, according to the Scimago-Institutions Ranking World Report 2021. CSIR holds the 7th rank in Asia and leads the country to the first position. CSIR has a dynamic network of 37 national laboratories, 39 outreach centres, 3 Innovation Complexes and 5 units with a pan-India presence. The notable achievement of CSIR is successfully challenged the grant of patent in USA for the use of Haldi (turmeric) for its wound healing property and insecticide. There are 21 CSIR divisions exclusively for the pharmacy related and 17 other departments. It is an integrated technology mission for the development of Ayurveda and traditional medical knowledge based on synchronized working of modern medicine & science and traditional medicine with special budgetary support. One of the funding agencies of CSIR is Golden Triangle Scheme which collaborates AYUSH – CSIR – ICMR. Only bonafide Indian citizens of 28 years with BS-4 years program/ BE/B. Tech/B. Pharma/MBBS can enter to the CSIR.